Body Shaming with Acceptance of Body Shape in Female Students - Dacosta, Maria Devika Donita; Keraf, M. K. P. Abdi; Damayanti, Yeni (Universitas Nusa Cendana, 2023)
Body shaming is an embarrassing experience that is focused on including feelings of shame, low self-confidence carried out by people around by ridiculing or insulting the physical and even the body shape of other individuals who look imperfect, this gives rise to the emergence of acceptance of body shape where individuals can feel satisfaction or dissatisfaction with body shape. This study aims to determine the relationship between body shaming and acceptance of body shape in female students. This type of research is quantitative with a correlational approach. The research participants were 198 female students at SMA Negeri 1 Kota Kupang aged 16-18 years. The sampling technique used purposive sampling. Collecting data using a body shaming scale consisting of 24 items (Cronbach' = 0, 873) and acceptance of body shape consisting of 28 items (Cronbach' = 0.888). Data analysis using Pearson correlation. The results of the analysis show a significant relationship between body shaming and acceptance of body shape in female students.